Randomized, Double-blind Pilot Study of Nanocurcumin in Bladder Cancer Patients Receiving Induction Chemotherapy - Sandoughdaran, Saleh; Razzaghdoust, Abolfazl; Tabibi, Ali; Basiri, Abbas; Simforoosh, Nasser; Mofid, Bahram (Urology Journal, 2021)
Purpose: To evaluate the feasibility and potential efficacy of nanocurcumin supplementation in patients with localized muscle-invasive bladder cancer (MIBC) undergoing induction chemotherapy. Materials and Methods: In this double-blind, placebo-controlled trial, 26 MIBC patients were randomized to receive either nanocurcumin (180 mg/day) or placebo during the course of chemotherapy. All patients were followed up to four weeks after the end of treatment to assess the complete clinical response to the chemotherapy as primary endpoint. Secondary endpoints were the comparisons of chemotherapy‐induced nephrotoxicity, hematologic nadirs, and toxicities between the two groups. Hematologic nadirs and toxicities were assessed during the treatment. Results: Nanocurcumin was well tolerated. The complete clinical response rates were 30.8 and 50% in the placebo and nanocurcumin groups, respectively. Although nanocurcumin was shown to be superior to placebo with respect to complete clinical response rates as the primary endpoint, there was no significant difference between the groups (p = 0.417). No significant difference was also found between the two groups with regard to grade 3/4 renal and hematologic toxicities as well as hematologic nadirs. Conclusion: These preliminary data indicate the feasibility of nanocurcumin supplementation as a complementary therapy in MIBC patients and support further larger studies. Moreover, a substantial translational insight to fill the gap between the experiment and clinical practice in the field is provided.